Wolbachia-induced reproductive parasitism and applications - Saridaki, A.; Bourtzis, K. (ENTOMOLOGIA HELLENICA, 2009)
Insects have been reported to be associated with a broad variety of microorganisms, affecting the host biology in many different ways. Among them, Wolbachia, an obligatory intracellular and maternally-inherited symbiont, has recently attracted a lot of attention. Beside insects, Wolbachia are found in association with a wide variety of other invertebrate species, including mites, scorpions, spiders, crustaceans, filarial nematodes. Several surveys have indicated that Wolbachia may be symbiont of up to 70% of all insect species, rendering Wolbachia the most ubiquitous intracellular symbiotic organism on Earth. Wolbachia-host interactions range from many forms of reproductive parasitism to mutualistic symbioses. Different Wolbachia strains have been found to induce a number of reproductive alterations such as feminization, parthenogenesis, male-killing or cytoplasmic incompatibility. Despite their common occurrence and major effects on host biology, speciation and ecological diversity, little is known on the molecular mechanisms that mediate Wolbachia-host interactions. Recent studies focus on the potential of Wolbachia-based methods for the biological control of insect pests and disease vectors of agricultural, environmental and medical importance.